'Greening' Fashion Discourse- An Exploration of Young German Consumers - Fritzsche, Laura Sophie (2011)
Abstract This dissertation explores the ways young German Consumers make sense of conventional fashion versus "green" or "sustainable" fashion. Four mini- Focus Groups were conducted with 18 participants that discussed their perceptions and experiences of fashion. The industry is one of the most environmentally damaging in the world and per head consumption of clothing has grown drastically in the last century, making it an important area for Sustainable Consumption research. The 16-27 year olds spend the largest percentage of their disposable income on fashion and accessories in Germany and are upcoming major consumers in other areas, too and thus a relevant group to look at in this context.